Programmable RNA editing with endogenous ADAR enzymes – a feasible option for the treatment of inherited retinal disease? - Bellingrath, Julia-Sophia; McClements, Michelle E.; Fischer, M. Dominik; MacLaren, Robert E. (Frontiers in Molecular Neuroscience, 2023)
RNA editing holds great promise for the therapeutic correction of pathogenic, single nucleotide variants (SNV) in the human transcriptome since it does not risk creating permanent off-targets edits in the genome and has the potential for innovative delivery options. Adenine deaminases acting on RNA (ADAR) enzymes catalyse the most widespread form of posttranscriptional RNA editing in humans and their ability to hydrolytically deaminate adenosine to inosine in double stranded RNA (dsRNA) has been harnessed to change pathogenic single nucleotide variants (SNVs) in the human genome on a transcriptional level. Until now, the most promising target editing rates have been achieved by exogenous delivery of the catalytically active ADAR deaminase domain (ADARDD) fused to an RNA binding protein. While it has been shown that endogenous ADARs can be recruited to a defined target site with the sole help of an ADAR-recruiting guide RNA, thus freeing up packaging space, decreasing the chance of an immune response against a foreign protein, and decreasing transcriptome-wide off-target effects, this approach has been limited by a low editing efficiency. Through the recent development of novel circular ADAR-recruiting guide RNAs as well as the optimisation of ADAR-recruiting antisense oligonucleotides, RNA editing with endogenous ADAR is now showing promising target editing efficiency in vitro and in vivo. A target editing efficiency comparable to RNA editing with exogenous ADAR was shown both in wild-type and disease mouse models as well as in wild-type non-human primates (NHP) immediately following and up to six weeks after application. With these encouraging results, RNA editing with endogenous ADAR has the potential to present an attractive option for the treatment of inherited retinal diseases (IRDs), a field where gene replacement therapy has been established as safe and efficacious, but where an unmet need still exists for genes that exceed the packaging capacity of an adeno-associated virus (AAV) or are expressed in more than one retinal isoform. This review aims to give an overview of the recent developments in the field of RNA editing with endogenous ADAR and assess its applicability for the field of treatment of IRD.